Enhanced anti-inflammatory activity of brown seaweed Laminaria japonica by fermentation using Bacillus subtilis. Issue 12 (December 2016) - Lin, Hong-Ting Victor; Lu, Wen-Jung; Tsai, Guo-Jane; Chou, Chien-Te; Hsiao, Hsin-I; Hwang, Pai-An
Graphical abstract: Highlights: L. japonica fermentation with B. subtilis enhance its anti-inflammatory effect. Cultivation parameters and nutrient additives were optimized for fermentation. L. japonica decreased ROS, NF-κB phosphorylation, PGE2, and NO production. Abstract: Most studies on the anti-inflammatory effects of Laminaria japonica have investigated bioactive ingredients that have been extracted from Laminaria using organic solvents. However, to avoid the toxicity and environmental issues caused by the solvent used for extraction, increasing attention has focused on fermentation using microorganisms as a green bioconversion process for producing bioactive compounds. In this study, fermentation with Bacillus subtilis, where the cultivation parameters and nutrient additives were optimized to achieve the greatest inhibition of lipopolysaccharide (LPS)-induced nitric oxide (NO) production, was found to enhance the anti-inflammatory effects of L. japonica . Fermentation by B. subtilis using a 5% (w/v) L. japonica suspension as the sole carbon source, 2% additional nitrogen source, a starting pH of 6, and incubation at 150 rpm at 37 °C for 72 h yielded the best anti-inflammatory effects, as LPS-induced NO production decreased to 27.6% ± 5.2%. The macrophages treated with the fermented L. japonica product inhibited the LPS-induced production of reactive oxygen species (ROS) and NF-κB (p65) phosphorylation in a concentration-dependent manner. Thus, our results show that L. japonica products generated by an optimized fermentation process designed to enhance anti-inflammatory effects by decreasing ROS production, NF-κB (p65) phosphorylation, prostaglandin E2, and NO production in macrophages.